Menggagas Descente Secara Elektronik - Anam , Ahmad Zainul (Judex Laguens, 2023)
The Supreme Court has significantly changed the administration of information technology-based justice. The Supreme Court's efforts to modernize Indonesian judicial procedures gave them a new look. Electronic site visits (descente) are one strategic innovation that the Supreme Court should consider to sustain the current trend of technological advancement. Yet, the concept and how to implement it must be thoroughly investigated. In light of this, this paper examines the concept and application of electronic descente. This qualitative literary study applies a literature technique, which comprises reading and comprehending documents or other works of literature related to the performance of descente or local inspection. The study's findings support some conclusions, including the following: First, while theoretically extremely feasible, electronic descente must wait for a legal foundation to become lawful before it can be implemented. Second, a few prerequisites must be completed before employing electronic descente. Third, not all civil cases are available for electronic inspection via descente. Fourth, there are advantages and disadvantages of using electronic descente.